Analisis Kerugian Energi pada Saluran Udara Transmisi Ekstra Tinggi 500 kv Gandul-Kembangan - Auliya Nabila (KOLONI, 2022)
Transmission lines are an important component in the distribution of electrical energy. The distance between power plants and loads depends on the length of the transmission line used. If the transmission line used is longer, the greater energy losses that occur and cause the energy reaching the loads decrease. The analysis of energy losses on the 500 kV extra high voltage transmission system from Gandul to Kembangan substation. The method is to calculate the induced voltage and induced current on the ground wire with transmission lines data using Carson Formula equation to determine the energy losses that occur on the Gandul-Kembangan 500 kV transmission lines. The results show that the energy losses are 831,2485 kW. Keywords: Transmission, Losses, Energy